Anglo-American relations since 1939 : the enduring alliance - Baylis, John 1946- (Documents in contemporary history, 1997)
Taking the 'special relationship' as a central theme, the book explores the public and private diplomacy between Britain and the United States in periods of war and peace. Using recently released archives as well as contemporary sources, the areas of both cooperation and conflict are revealed. What emerges is a much more complex relationship than the one normally portrayed in much of the secondary literature on the subject. The documents also reveal the way the concept of the 'special relationship' was used as a 'tool of diplomacy' on both sides of the Atlantic.